Exploring the Nexus of Financial Management, Understanding of Technology, and the Role of Governance in Shaping MSME Performance (Jurnal Cendekia Keuangan, 2026)
Introduction/ Main Objectives: This study analyzes the performance of MSMEs in West Celebes Province by examining financial management, technological adoption, and government support. Given the strategic role of MSMEs in regional economic growth and their ongoing challenges, the study investigates how these factors influence MSME performance. Novelty: This study offers a comprehensive analysis by integrating financial management, technological understanding, and government support into a single empirical model, specifically within the context of MSMEs in West Celebes. Previous studies have often examined these factors separately, leaving a gap in understanding their combined effect in a regional setting. Research Methods: This study employs a quantitative approach using primary data collected from 121 MSME respondents through purposive sampling. Data were gathered using structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine relationships among variables. Finding/Results: The findings show that financial management, technological adoption, and government support each significantly enhance MSME performance, indicating that improvements in these areas are strongly linked to better business outcomes. Conclusion: This study concludes that sound financial management, stronger technological capability, and active government support are key drivers of MSME performance. Enhancing these factors fosters the sustainability and growth of MSMEs in West Celebes.